Simplified Antibiotic Regimens for the Management of Clinically Diagnosed Severe Infections in Newborns and Young Infants in First-level Facilities in Karachi, Pakistan: Study Design for an Outpatient Randomized Controlled Equivalence Trial - Zaidi, Anita K. M. (Williams & Wilkins, 2013)
BACKGROUND: Infection in young infants is a major cause of morbidity and mortality in low-middle income countries, with high neonatal mortality rates. Timely case management is lifesaving, but the current standard of hospitalization for parenteral antibiotic therapy is not always feasible. Alternative, simpler antibiotic regimens that could be used in outpatient settings have the potential to save thousands of lives. METHODS: This trial aims to determine whether 2 simplified antibiotic regimens are equivalent to the reference therapy with 7 days of once-daily (OD) intramuscular (IM) procaine penicillin and gentamicin for outpatient management of young infants with clinically presumed systemic bacterial infection treated in primary health-care clinics in 5 communities in Karachi, Pakistan. The reference regimen is close to the current recommendation of the hospital-based intravenous ampicillin and gentamicin therapy for neonatal sepsis. The 2 comparison arms are (1) IM gentamicin OD and oral amoxicillin twice daily for 7 days; and (2) IM penicillin and gentamicin OD for 2 days, followed by oral amoxicillin twice daily for 5 days; 2250 “evaluable” infants will be enrolled. The primary outcome of this trial is treatment failure (death, deterioration or lack of improvement) within 7 days of enrollment. Results are expected by early 2014. DISCUSSION: This trial will determine whether simplified antibiotic regimens with fewer injections in combination with high-dose amoxicillin are equivalent to 7 days of IM procaine penicillin and gentamicin in young infants with clinical severe infection. Results will have program and policy implications in countries with limited access to hospital care and high burden of neonatal deaths.